Paleomagnetism and geochronology of the Late Cretaceous-Paleogene island arc complex of the Kronotsky Peninsula, Kamchatka, Russia: Kinematic implications (Dataset) ... - Levashova, Natalia M.; Shapiro, Mikhail N.; Beniamovsky, Vladimir N.; Bazhenov, Mikhail L. (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetism and geochronology of the Late Cretaceous-Paleogene island arc complex of the Kronotsky Peninsula, Kamchatka, Russia: Kinematic implications ...